Analysis of Accounting Treatment of Drug Inventory Based on PSAP No. 5 and the Application of SOP at the Dinas Kesehatan Kabupaten Banyumas - Muninggar, Wisang Setya; Dirgantari, Novi; Setyadi, Edi Joko (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to analyze the accounting treatment of drug inventories at the Dinas Kesehatan Kabupaten Banyumas by examining its compliance with Government Accounting Standards Statement (PSAP) No. 5 and the agency’s internal Standard Operating Procedures (SOP). The research method used is a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The results showed that inventory recognition is carried out after the goods are fully received in accordance with the order and supported by official documents, as stipulated in Government Accounting Standard No. 5. Inventory measurement uses the acquisition cost method which includes purchase price, transportation costs, handling, and taxes, and the recording method used is First In First Out (FIFO). In addition, the disclosure and expense of inventory has been carried out according to the standard, including the recording of damaged, expired, and non-consumable goods. Recording is done on a perpetual basis, allowing real-time tracking of item mutations. This study concludes that overall, the management of drug inventories at the Dinas Kesehatan Kabupaten Banyumas has been carried out accountably and in accordance with the provisions of PSAP No. 5 and the applicable SOPs.